Dampak Kegiatan Pembiasaan Tadarus Al-Qur’an terhadap Sikap Keagamaan Siswa SMP Kosgoro - Fahmi, Hannan Misbakhul; Hidayah, Nurul; Chotimah, Chusnul (Lembaga Yasin AlSys, 2025)
This research is motivated by the importance of cultivating the habit of Qur’anic recitation (tadarus Al-Qur’an) in schools as a means of shaping students' religious attitudes and understanding the impact of this habit. The aim of this study is to explore how the implementation process of Qur’anic recitation habits is carried out at SMP Kosgoro and to identify the impact of tadarus Al-Qur’an on the religious attitudes of students at SMP Kosgoro. This study employs a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving the principal, curriculum coordinator, homeroom teachers, and students of SMP Kosgoro. The data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results of this study indicate that: (1) The implementation of the Qur’anic recitation habit is carried out before the start of lessons, with an allocated time of 15 minutes. The purpose of this activity is to instill religious values in students and to familiarize them with reading the Qur’an, thereby improving their Qur’anic reading skills. (2) The impacts of this habitual tadarus activity on students' religious attitudes are as follows: a) It enhances students’ discipline. b) In terms of religious behavior, the activity fosters more polite, orderly behavior and respect toward teachers and peers, both at school and at home. c) In terms of religiosity, students become more diligent in worship, such as regularly performing Dhuha prayers, reading the Qur’an, and increasing their piety. d) Reading the Qur’an before lessons creates a sense of calm, helping students to concentrate better during class.